A novel hyper-viscoelastic model for consolidation of toughened prepregs under processing conditions. (June 2016) - Belnoue, J.P.-H.; Nixon-Pearson, O.J.; Ivanov, D.; Hallett, S.R.
Highlights: A new modelling framework for resin flow in uncured toughened prepreg is proposed. The paper focuses on prepreg volumes characteristic of materials produced by AFP, tapered and shape transition regions. Squeezing and bleeding flow mechanisms are present simultaneously. The model is implemented as a hyper-viscoelastic model into a UMAT subroutine for Abaqus. The model paves the way towards prediction of fibre path defects driven by excess length creation during consolidation. Abstract: The paper presents a new modelling concept for describing the compressibility of toughened uncured prepregs over a wide range of processing conditions (i.e. automatic fibre deposition, hot debulking and pre-curing consolidation). The primary challenge of the work is to simulate the material response due complex flow and deformation mechanisms. This generation of prepreg systems exhibits both percolation (bleeding) flow typical for conventional thermosets, where the pressure gradient causes resin flow relative to the fibres, and shear (squeezing) flow typical for thermoplastics, where the laminate behaves as a highly viscous incompressible fluid. As a result, it holds features of both the systems: e.g. a convergence to a certain compaction limit at high temperatures and pressure levels and size/ply configuration-dependent material response. The modelling starts from micro-structural considerations, which give the foundation for an analytical model that assumes a transition from percolation to shear flow. It is shown that this model can capture the material behaviour very well. A hyper-viscoelastic material model is then constructed and implemented within the finite element package Abaqus/Standard. The model parameters are identified from an experimental programme and validated against compaction experiments over a wide range of load rates, temperatures and laminate configurations.